A Participação da mulher na microeconomia rural: estudo multicaso em Tauá-Ceará - Soares, Marciana de Lima (2014)
The effective participation of women in the rural economy even considered in conjunction with the numerous advances made by official rural statistics was not yet sufficient to its recognition as the protagonist of the national, regional and local economic development. This study seeks to highlight through study in loco, the strength of the labor of women in rural microeconomics. 96 Rural Households (UPAFs) distributed between 6 communities in the District of the Baixo Trici (Municipality of Taua), CE, namely: Junco (n= 22), Tapera (n= 22), Lustal I (n= 19), Lustal II (n= 8), Tiassol (n= 15) and Queimadas (n= 10) were studied. The total of UPAFs existing in these communities amounts to 305, therefore, the present study covered 31,47% of districts\'UPAFs. The initial hypothesis was that rural women as active and relevant to the economic development of the state of Ceará, and in particular, to the municipality of Taua. Thus, the main purpose was to characterize the work profile of rural women of these UPAFs through the statistical typification associated to micrologistics implications. Original data field that generated economic variables were used on which applied statistical study by means of the Principal Components Analysis (ACP) and Cluster was made. With the obtained results, a detailed interpretation was presented attaching the economic profile of the woman in her historical reasoning and totaling the logistical management of internal real female participation in rural microeconomics. The grouping of UPAFs resulted in four groups as typified and qualified so that the G1 was considered to be the group with the highest rate of Familiar Work Unit and female with emphasis on the labor of the woman in the Production of Small Ruminants and marketing of its derivatives. The G2 was characterized as the largest number of UPAFs with reverse production in relation to total productivity. In addition, in this group the multifunctionality of the woman in productive aspects is relevant. The largest useful area was the strong characteristic pointed to the G3 and consequently greater plant production and female work little evidenced in large territorial dimensions. Finally the G4 with a greater variety and productive participation of the woman representing multiple functions: in partnership with the Work Unit employed and highlight in administrative activities. There are strong indications about the lack of recognition and devaluation of woman labor at the level of Ceará, Brazil and the World. It is recommended that punctual actions were prioritized in relation to the rural woman, as well as the logistic operational structure in favor of optimizing and qualification of the work performed by her. In this way it is necessary to intensify the research showing the female reality within rural environment and accentuating the many struggles and movements in favor of the woman’s appreciation and consequently improvements aggregated to Family Farming